If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -7 = -8 + x Combine like terms: -6 + -7 = -13 -13 = -8 + x Solving -13 = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -13 + -1x = -8 + x + -1x Combine like terms: x + -1x = 0 -13 + -1x = -8 + 0 -13 + -1x = -8 Add '13' to each side of the equation. -13 + 13 + -1x = -8 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = -8 + 13 -1x = -8 + 13 Combine like terms: -8 + 13 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| -7-y=6 | | (2x^3)+(6x^2)-x-8=0 | | 11log(3x+4)=2 | | 11+3=-2.5 | | 6x+72.48=18.08 | | Y=.75x+4.5 | | 20x+10=9+7x | | 20=5x+3(x-12) | | -7-6=6 | | 5x+10=9+7x | | 7x+5=1+5x | | 7x+5=2+5x | | 8x+5=1+5x | | 0.07c=14 | | 20x+30=20+8 | | 20x+15=300-8 | | 20x+15=100-8 | | [x+25]+55=180 | | lnx*2x^2=0 | | (5w-9)(6+w)=0 | | 102+9m=273 | | 28n-221=255 | | 9x-2=36-10x | | y^5-xy-x^3=-8 | | 19=9w-5+6w | | 2x-33=29 | | (2x-10)=(x-20) | | Ydy=2(x+y)dy | | m-7m-2m+7= | | 3n-11=58 | | 2x-4+4x=0 | | y[n]=0.5x[n]+0.5y[n-1] |